Decolonizing Social Sciences in postcolonial countries: Reflection on the Social Sciences in Indonesia (Research, Society and Development, 2022)
This study re-scrutinizes the construction of social sciences in Indonesia determined the face of Indonesia today. The aim is to reveal power relations between the power regime and the the social sciences of production in Indonesia through discourse and historical dimensions, because the discourse dimension determines what is called true by a knowledge regime, while the historical dimension reveals the political context. The method used is qualitative research, while the approach used is decolonizing interpretative approach. This approach focuses on three things, namely: the critical influence on the hegemonic knowledge regime, the historicity of knowledge created from a certain social context, and the political economy that determines the interest of knowledge. The results of this study are (1) there are three hegemonic paradigms in the development of social sciences in Indonesia, namely; the Indological paradigm introduced by the Dutch colonial government, the modern social science paradigm introduced by the United States (US), and the contemporary social science paradigm under the influence of the market (neoliberalism); (2) as a response to the three paradigms, Indonesian intellectuals formulated a decolonization project which was articulated in three forms, namely; the indigenization of social sciences was initiated by the researchers at Indonesian Institute of Sciences, Nusantara Philosophy was initiated by the scholars at the Faculty of Philosophy, Universitas Gadjah Mada University, and the Islamization of knowledge or the integrated knowledge was initiated by the muslim scholars at the Islamic States Universities.